Clinical Evidence for the Microbiome in Inflammatory Diseases - Slingerland, Ann E.; Schwabkey, Zaker; Wiesnoski, Diana H.; Jenq, Robert R. (Frontiers in Immunology, 2017)
Clinical evidence is accumulating for a role of the microbiome in contributing to or modulating severity of inflammatory diseases. These studies can be organized by various organ systems involved, as well as type of study approach utilized, whether investigators compared the microbiome of cases versus controls, followed patients longitudinally, or intervened with antibiotics, prebiotics, or bacterial introduction. In this review, we summarize the clinical evidence supporting the microbiome as an important mechanism in the onset and maintenance of inflammation.